Online Performance Learning on E- Learning Systems - Abduvaliyevich, Medatov Asilbek (European Journal of Life Safety and Stability (2660-9630), 2021)
Education is generally perceived as the method whereby we have the student deliver lessons from within the classroom to the Teacher, but with the facilitating information technology over the Internet, learning can now be achieved without a significant qualifying teacher in the eyes of the student. E-learning is one of the tools that emerge from information technology and have been integrated into many university educational programs, a change from the traditional approach to education in an electronic environment in which the student can receive and use information anywhere and anytime. The aim of an e-learning management system is to streamline the existing manual circuit with computerized hardware and full-fledged computer software that suits their requirements, so that their valuable data / information can be stored from a long era with easy access and manipulation of the same. The required software and hardware is easy to obtain and easy to operate. An e-learning management system, as described above, can lead to free, secure, consistent and fast management classification. He can support the user to discuss their other actions moderately, to think about checking the accounting. Thus, it resolves to help the organization improve the use of resources. The organization can keep computerized records without unnecessary records. This means that you do not need to be distracted by information that is not relevant to the case, but at the same time be able to reach the information. It can help to collect perfect control in particulars. In a very short time, the assortment will be noticeable, simple and reasonable. This will help the person to understand the management of the past year absolutely and vividly. It also helps with the ongoing work related to the eLearning management system. The cost of accumulating management and collection practices will also be reduced.